Electrospun poly(methyl methacrylate) fibrous mat showing piezoelectric properties. (19th April 2018) - Nobeshima, Taiki; Ishii, Yuya; Sakai, Heisuke; Uemura, Sei; Yoshida, Manabu
Abstract: A piezoelectric effect, such as actuation behavior with voltage application, could be observed from a poly(methyl methacrylate) (PMMA) fibrous mat fabricated by electrospinning. This fibrous mat increased or decreased its thickness in accordance with the polarity of the applied voltage, which appears to be an inverse piezoelectric effect. The appearance d T constant was as large as 8.5 nm/V owing to the softness of the fibrous structure, and the coupling constant K T = 0.31 indicated its efficient piezoelectric property. This piezoelectric behavior was repeatedly observed to be stable at room temperature. In addition, the polarization components of the fibrous mat, which are considered to be the origin of its piezoelectric effect, and its relaxation behavior were confirmed from the results of thermally stimulated current measurements.